Investigation of the C3+ Auger KLL spectrum obtained in collisions of 6-15 MeV C4+ (1s2, 1s2s 3S) with gas targets - Madesis, I.; Laoutaris, A.; Benis, E. P.; Zouros, T. J. M. (HNPS Advances in Nuclear Physics, 2019)
Single electron transfer to the 1s2s 3S long-lived component of the naturally occurring mixed-state(1s2, 1s2s 3S) C4+ion beam in collisions with gas targets was investigated using zero-degree Auger projectile spectroscopy at the Demokritos 5.5 MV tandem accelerator. The observed KLL Auger spectrum contains 1s2s2p 2P and 4P states resulting from direct 2p transfer to the 1s2s 3S. Higher lying (1s2s 3S)nl2,4L states produced by nl transfer (n>2) were also observed and can in principle feed the lower lying 1s2s2p2Pand 4Pstates. However, due to spin selection rules only the quartets have large enough radiative branching ratios resulting in a proposed selective feeding of only the 1s2s2p 4P state by E1 cascades, while minimally affecting the 1s2s2p 2P states. In the absence of cascades, the ratio of cross sections for 2p transfer to the 1s2s 3S state, Rm≡ σm(4P)/σm(2P), is 2 according to spin statistics. However, the 1s2ground state beam component also contributes to the production of the 1s2s2p 2P doublet states by transfer-excitation. To isolate just the 1s2s 3S transfer contribution and compute Rm, a new technique was employed requiring the recording of two KLL spectra, with the same collision energy, but each with appreciably different 1s2s 3S content, varied by stripping techniques. Our determination of Rmshows this to be >2, in agreement with spin statistics, but contrary to the expected 4P enhancement due to cascade feeding. Details of the analysis and results are discussed.